Demonstrating managed aquifer recharge as a solution to water scarcity and drought: description of Marsol project demo sites in Portugal - Leitão, T. E. (2015)
This paper presents a synthesis of the work developed in Portugal, by LNEC, TARH and UAlg, for the European Union Seventh Framework Programme project "Demonstrating Managed Aquifer Recharge as a Solution to Water Scarcity and Drought – MARSOL". The main achievements gathered in the DEMO sites during 2014, the first year of the project, are briefly presented.